Ocular tissue distribution and pharmacokinetic study of a small 13kDa domain antibody after intravitreal, subconjuctival and eye drop administration in rabbits. (February 2018) - Gough, Gerald; Szapacs, Matthew; Shah, Tejash; Clements, Peter; Struble, Craig; Wilson, Robert
Abstract: Domain antibodies (dAb's) comprise the smallest functional unit of human IgG and can be targeted to a range of different soluble cytokine and receptor targets in the eye. In particular their small size may offer advantage for ocular tissue penetration and distribution. To investigate this we used a 13kDa tool molecule to undertake a preliminary short term ocular tissue distribution and pharmacokinetic study in the rabbit eye. The dAb was administered by the intravitreal or subconjunctival route or, as topical eye drops for up to five days and dAb concentrations measured in vitreous, aqueous, conjunctiva, choroid-RPE, retina, iris, sclera, and ciliary body. The observed elimination half-live of the dAb (~3 days) in vitreous showed a similar elimination rate to that of a much larger (∼50kDa) Fab fragment whilst the half-life following subconjunctival administration was ∼24 h and, after eye drop dosing the dAb was detectable in aqueous and conjunctiva. These preliminary data show that the intravitreal half-life of dAb's are similar to much larger antibody fragments, offering the potential to deliver significantly more drug to target on a molar basis with a single intravitreal injection potentially enabling dosing frequencies of once a month or less. Subconjunctival injection may provide short duration therapeutic levels of dAb to the anterior and posterior chamber whilst topical eye drop delivery of dAbs may be useful in front-of-eye disease. These data indicate that small domain antibodies may have utility in ophthalmology. Further studies are warranted.